The U.S.-Iraq War’s Legacy in Global Terrorism and the Taliban’s Return to Power - Sadaghashvili, Tamuna (European Scientific Journal, ESJ, 2025)
The 2003 U.S.-Iraq War, initiated with claims of eliminating weapons of mass destruction and removing Saddam Hussein, has had lasting effects that influence global security today. Although the main military objectives were quickly met, the war’s long-term consequences extended well beyond Iraq itself. This article explores how the invasion and occupation unintentionally fostered an environment conducive to terrorism - not just in Iraq but throughout the region and worldwide. Actions like disbanding Iraq’s military, alienating Sunni communities, and increasing sectarian violence fueled the rise of radical groups such as ISIS, which exploited instability and grievances to consolidate power. Meanwhile, the extended U.S. military involvement in the Middle East drew focus and resources away from Afghanistan, hampering efforts to establish lasting governance and security. This diversion enabled the Taliban to reorganize, strengthen, and eventually retake power in 2021 after U.S. forces withdrew. The analysis highlights how these two major conflicts are linked, showing that policy choices from the early 2000s unintentionally strengthened the very extremist groups they sought to oppose. By examining the unintended effects of the Iraq War and its connection to the Taliban’s resurgence, this paper highlights the broader impacts of military intervention, the intricacies of state-building in conflict zones, and the long-term obstacles in the global fight against terrorism. Grasping these links is essential for developing more effective and responsible foreign policy in the future.